Jane’s body-territory: space, gender and power in The Assistant - Riveres, Rosa (2022)
The purpose of this article is to analyze how bureaucratic spaces reproduce discourses, showing that, in terms of gender, they do not correspond to innocuous spaces, given that there are normative representations that provide elements of the ideology of domesticity and maternalization of women transmitted through social discourses, supported by representations such as cinema. It is important here to analyze the representation of the secretary in the film The Assistant in order to characterize the specificities that arise from its construction, based on practices related to the (re)presentation of the body-territory and the deployment in the use of public/private space in the protagonist of the film. For this purpose, the Relief Maps tool (Rodó-Zárate, 2013, 2021) is applied, intersecting the categories of gender, age and social class with the places that figure most in the film. It emerges that by following a notion of the passive-active complement of women with respect to men, the hierarchical structures in which the secretary is immersed and of the hetero-normative model as the basis of social relations in the public sphere are also unequal subjects/actors representing a paradox in itself. Although they participate in common spheres of mitigation of their own vulnerabilities associated with structural factors, regarding the patriarchal culture.